INTERDISCIPLINARITY IN DESIGN AS A CHALLENGE FOR PROFESSIONALISM - AN EXAMPLE OF INTERFACE DESIGN - Strode, Aina; Romančenko, Margarita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The need for diverse knowledge and skills in the work of a designer is a problem in vocational education, which mainly focuses on the artistic aspect of design. The aim of this article is to analyze the specifics of User Interface Design, its relation to User Experience Design, to determine the User Interface designer professional skills and how to acquire them. Research methods – theoretical: literature research; empirical – questionnaire. Exploring educational opportunities in Experience Design and User Interface Design demonstrates the need for Video game Interface study programs, particularly in the Latvian context. As the curriculum is traditionally designed for narrowly focused specialization, it would be appropriate to develop study modules for User Interface Design that include acquiring both graphics, game design and programming skills. The results of the video game developer survey demonstrate the role of practice in improving professional experience.